Humanizing RRI in mega engineering projects: insights from the Hong Kong-Zhuhai-Macao Bridge project - Ping Li; Ziqiang Zhao (Journal of Responsible Innovation)
Humanizing Responsible Research and Innovation (RRI) emphasizes the micro-level actions of actors. Its essence involves underscoring a practice-oriented approach, opening the ‘black box’ of the subjects of responsibility in RRI, and exploring the duality between structure and agency in the practice of implementing responsibility. Through a case study of the construction of the Hong Kong-Zhuhai-Macao Bridge, these three characteristics were reflected in the structured Health, Safety and Environment system of the project and related agentic actions. The case study also revealed two types of agency: compliance and suitability of the subject of responsibility. Implementation of RRI does not simply apply a framework (e.g. Anticipation, Inclusiveness, Reflexivity, and Responsiveness, AIRR) in a top-down manner, but combines the heuristic ideas of AIRR with local actors’ practices to form a feasible restrictive institution.